Pertanggung Jawaban Direksi dalam Perseroan Terbatas dan Perspektif Hukum Korporasi - Prakasa , Ragil Surya; Farni, Fatimah Hayati; Gusherva , Ramizah Kamelia; Daitu, Apin Rahmat; Aditya, Rizky Bintang (PUAN INDONESIA, 2024)
A company is a legal entity (rechtspersoon) which is a legal subject other than Humans, like corporate people, can also be subject to rights and obligations, and Just like humans, companies can be held responsible if they are proven to have done something errors and causing losses, including liability for criminal acts. Company In its business activities it certainly does not operate alone, there is a management who is the "master" for it company to carry out its business activities, one of the management is the Board of Directors. Writer Through this article, we try to discuss the meaning of corporate criminal acts, the responsibility of directors in the Limited Liability Company Law for their actions in running a company, after that the author will discuss the responsibility of directors for a criminal acts committed by companies or what are commonly referred to as corporate crimes. The responsibility of directors in a company is very crucial, because para Directors have great power in managing company resources and determining strategic direction. As company leaders, they have inherent legal obligations on them to act in good faith, perform duties with skill and wisdom, and are morally and legally responsible for their actions. In In practice, the responsibilities of directors in a company cover a number of diverse aspects. First, they must carry out their company management duties with great care and attention based on the company's interests. Directors must make rational and rational decisions based on careful consideration, with the aim of maintaining the continuity of the company's business and increase company value in the long term.